Effect of Additional Natural Filler Waste on The Mechanical Properties of Polyurethane Polymer - Mohammed, Ahmed J.; Muhsen, Muhsen Chelab; Ibrahim, Ibrahim K. (Bumi Publikasi Nusantara, 2023)
The mechanical properties of polyurethane/conocarpus leaf composites were studied. The conocarpus leaf powder was mixed with 0-55% of polyurethane. The best ratio was obtained when using 45-55%. The obvious improvement in the mechanical parameters was recorded when adding conocarpus leaf powder with 55% of polyurethane. The properties of polyurethane/conocarpus leaf composites were analyzed as a function of the additional ash amount. All prepared composites showed improved ash dispersion in the polyurethane matrix. The highest value of the compressive strength was when the ratio of 45%, reaching 9.82 MPa. This is because of this homogeneity rate between conocarpus leaf powder and chains of the polymer. The lowest value was obtained, reaching 3.3 MPa when using 30%.